Otoritas Hula-Hula dan Teologi Berkat: Tinjauan Dogmatis Tentang Relasi dan Karunia Allah dalam Konteks Budaya Batak Toba - Boby Andika Sinaga; Henri Naibaho (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the role of the hula-hula authority within the Batak Toba kinship system, known as Dalihan na tolu, and its relevance to the theological understanding of blessings. In Batak tradition, hula-hula is viewed as